Balancing leadership patterns to promote sense of community during cell-church transitioning: a grounded theory of strategic leadership and change - Pearse, Noel J (Rhodes University, Faculty of Education, Department of Education, 2006)
The aim of this research was to develop a substantive grounded theory describing the process of change and the management of organizational inertia, or resistance to change, by strategic leaders transitioning churches from a programme-based to a cell-based model. The grounded theory was developed using the conventions of the Straussian version of the grounded theory method, and relying largely upon the collection of incidents through interviews with leaders of churches that embarked upon the cell-church transition. In all, 38 interviews were conducted with leaders of churches representing a range of denominations located in a number of provinces in South Africa. Based on the premise that substantive theories are contextually bound rather than context free, the contextual characteristics of this study are highlighted. Drawing from organizational theory, it is recognised that churches can be conceptualised as solidary organizations, normative organizations, congregations and voluntary organizations or associations. Viewing churches as solidary organizations highlights the role of solidary rewards in the change process, while viewing them as congregations, emphasises their religious character. Furthermore, the context of the study is embedded in the nature of the specific type of change being embarked upon, as represented by the cell-church transition. Drawing on concepts derived from the change management literature, the type of change I investigated, I classified as intangible, episodic, teleological, second-order change, highlighting the importance of social interaction. The grounded theory that was constructed describes the phases of the change process, and how the actions of leaders interact with the sense of community of the church. Three effective patterns of leadership were identified (i.e. the freewheeler, the focused-pioneer and the reflexive-accommodator) along with their ineffective counterparts (i.e. the static non-leader, the rigid combatant and the popular people pleaser). It was argued that effective leadership involves balancing the three effective patterns over time, and that a failure to achieve this balance produced an ineffective pattern. Furthermore, ineffective leadership damaged the credibility of leaders, as their actions harmed the sense of community. A loss of credibility compromised the leader's ability to lead change. A number of approaches to understanding organizational inertia or resistance to change were examined in an attempt to locate the grounded theory in the literature and to use the literature to shed light on the findings of this study. While this literature did provide some useful insights and confirmations, no single theoretical perspective seemed to supply a comprehensive explanation. Instead, social capital theory offered a more encompassing explanation, and as such, showed much promise as a body of literature that can be used to develop an understanding of organizational change. Finally, recommendations are made for future research and the value of this research is discussed.
Keywords: Leadership -- South Africa; Christian leadership; Church management; Strategic planning -- South Africa; Grounded theory; Organizational change -- South Africa